Development of the service economy in Kazakhstan - Christian, Brauweiler Hans; S, Mukhtarova K.; A., Yerimpasheva A. (Farabi Journal of Social Sciences, 2019)
The modern world is an integrated universal network of various world markets. The rapid development of the service sector is a distinctive trend of the global economy. All the evidence suggests that a specific economic model, the economy of services is formed. The purpose of the study is critically analyse theories in relation to servitization processes that take place in the world and the republic of Kazakhstan. Studying of world trends and tendencies would help to enhance the Kazakhstani economy. It is used time-series analysis of the gross domestic product’s (GDP) structure and noted that developed and developing countries differ in terms of the GDP structure. Despite of the high level of the service sector’s proportion in the structure of the Kazakhstan’s GDP, the share of investments in the sector is declining. The implemented study has recognized problems the Kazakhstani economy faces. Directions to improve the current situation are suggested. Key words: servitization, service economy, service sector, productivity of service, innovation in services, “service know‐how”.